2021
DOI: 10.1177/09544070211035859
|View full text |Cite
|
Sign up to set email alerts
|

Research and modeling of tire cornering characteristics considering tread wear based on UniTire model

Abstract: In view of the complexity of tire structure and working conditions, tire models are often based on complete and accurate test data. In combined with the theory of tire dynamics, the empirical and semi-empirical tire models are built. In order to accurately measure the tire mechanical properties, it is necessary to strictly control the wear state of the tire tread during the tire test. But there is still a certain amount of wear, which does not guarantee the consistency of the data. In order to study the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The cornering stiffness and aligning stiffness of each tire under different loads are shown in the Figure 7. By comparing the cornering stiffness and aligning stiffness under different loads, we not only confirmed the conclusion similar to that in [30], which indicates that both cornering stiffness and aligning stiffness increase proportionally with tire wear, but also found that the magnitude of the changes varies under different loads. Furthermore, an even more interesting observation was made.…”
Section: Cornering Characteristics Of Worn Tiressupporting
confidence: 84%
See 1 more Smart Citation
“…The cornering stiffness and aligning stiffness of each tire under different loads are shown in the Figure 7. By comparing the cornering stiffness and aligning stiffness under different loads, we not only confirmed the conclusion similar to that in [30], which indicates that both cornering stiffness and aligning stiffness increase proportionally with tire wear, but also found that the magnitude of the changes varies under different loads. Furthermore, an even more interesting observation was made.…”
Section: Cornering Characteristics Of Worn Tiressupporting
confidence: 84%
“…Cornering characteristics are one of the important mechanical properties that seriously affect the handling stability. Lu et al [30] extended the wear conditions of the UniTire tire model and examined how different wear conditions affected cornering stiffness and aligning stiffness. The analysis was then compared with experimental data to validate the model's accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…On a similar note, in 2022, Lu et al (2022) developed a semiempirical model using experimental values, tire footprint pressure distributions, and the brush model to estimate a tire block's wear. However, in 2011, Matilainen and Tuononen (2011), combined the brush model with the bicycle model to estimate tire wear friction.…”
Section: Simulated Tire Wear Modelingmentioning
confidence: 99%